On Further Improvement of the Technique of Evaluating Summer Institutes - IYER, H KRISHNA; KAUL, P N (Fishery Technology, 2017)
Data from an earlier study are reanalyzed to improve upon the evaluation measures of summer institutes. The Summer Institute Efficiency Index is improved by using weighted geometric mean using different ranks as weights for the several dimensions. The coverage utility index is improved by taking the ratings given by all the participants.